Growth of Slipper Orchid Paphiopedilum javanicum (Reinw. ex Lindl.) Pfitzer during Acclimatization Stage - Hendriyani, Ema; Warseno, Tri; Oktavia, Gebby Agnessya Esa (Jurnal Biodjati, 2019)
Â Paphiopedilum javanicum (Reinw. ex Lindl.) Pfitzer known as slipper orchid is an endemic terrestrial orchid from Indonesia. This orchid is threatened with extinction and listed under CITES Appendix I. In-vitro propagation of P. javanicum has been done in Bali Botanic Garden (BBG) for last six years but acclimatization stage has not given satisfied result. The purpose of this study was to know the ef-fect of liquid fertilizer on vegetative growth of P. javanicum planlet during acclimatization stage. Beyonic StarTmik liquid fertilizer ap-plied by five different doses considered as treatment of 0, 10, 20, 30 and 40 mL. They were 10 planlets for each treatment considered as replication. In this research we observe vegetative growth of P. ja-vanicum by quantitative and qualitative parameter. Quantitative data were analysis by ANOVA. Result showed, high percentage of planlet survival was observed of 98% and liquid fertilizer dose for 30 mL gave the optimal vegetative growth of P. javanicum planlet with aver-age height of 2.2 cm and leaves number of 13 pieces. There were no differences on qualitative parameter in all treatment that all leaves color was dark green and leaves tessellation appearance was obviousÂ 